Comparative study of the strain signal and the edited strain signal - Muhamad Faizal, Abd Ghani (2012)
This study presents the comparative study between the original strain signal and its edited strain signal. In this study, the data of fatigue strain loading on an automobile coil spring was used and the purpose to this component is because it been identified as one of the critical component in an automobile. The strain signal editing process was performed by removing low amplitude cycles were eliminated based on the cut-off level of the signal energy distribution in the time representation. Thus, the new edited signal was obtained which has retained almost 100% of the original fatigue damage and has equivalent signal statistic. The original and edited strain signals were analysed for predicting the fatigue damage of the coil spring. A comparison study of the fatigue damage and the highest damage zone obtained from the original strain signal and the edited strain signal carried out. From the result obtained, the prediction of the fatigue damage and the highest damage zone for both strain signals original and edited is equivalents. Hence, for the laboratory fatigue testing the shortened signals that was produced from damage editing process can be used as a tool to accelerate the fatigue testing.